Orientation effects on the near-infrared broad-band emission of quasars. Issue 1 (17th February 2019) - Bisogni, Susanna; Lusso, Elisabeta; Marconi, Alessandro; Risaliti, Guido
Abstract: We recently proposed the equivalent width (EW) of the narrow [O iii ]5007 Å emission line as an orientation indicator for active galactic nuclei. We tested this method on about 12 300 optically selected broad-line quasars from the SDSS seventh Data Release at redshift z < 0.8 and with full width at half-maximum values of broad emission lines (H α, H β, and Mg ii ) larger than 2000 km s −1 . We now examine their spectral energy distributions (SEDs) using broad-band photometry from the near-infrared to the ultraviolet to look for variations in the overall shape as a function of the EW[O iii ]. We find that quasars with low EW[O iii ] values (close to face-on position) have flatter near-infrared SEDs with respect to sources with high EW[O iii ] values (almost edge-on). Moreover, quasars with high EW[O iii ] values show a factor of ∼2 lower emission in the UV to quasars with low EW[O iii ] values. Our findings indicate that the torus is clumpy and, on average, co-axial with the accretion disc and broad-line region, in agreement with the most recent theoretical models for the obscuring torus.